Plant stress responses and phenotypic plasticity in the Epigenomics era: perspectives on the grapevine scenario, a model for perennial crop plants - Fortes, Ana M.; Gallusci, Philippe (Frontiers in Plant Science, 2017)
Epigenetic marks include Histone Post-Translational Modifications and DNA methylation which are known to participate in the programming of gene expression in plants and animals. These epigenetic marks may be subjected to dynamic changes in response to endogenous and/or external stimuli and can have an impact on phenotypic plasticity. Studying how plant genomes can be epigenetically shaped under stressed conditions has become an essential issue in order to better understand the molecular mechanisms underlying plant stress responses and enabling epigenetic in addition to genetic factors to be considered when breeding crop plants. In this perspective, we discuss the contribution of epigenetic mechanisms to our understanding of plant responses to biotic and abiotic stresses. This regulation of gene expression in response to environment raises important biological questions for perennial species such as grapevine which is asexually propagated and grown worldwide in contrasting terroirs and environmental conditions. However, most species used for epigenomic studies are annual herbaceous plants, and epigenome dynamics has been poorly investigated in perennial woody plants, including grapevine. In this context, we propose grape as an essential model for epigenetic and epigenomic studies in perennial woody plants of agricultural importance.